Religious Views on Dan Brown’s The Da Vinci Code (2013): Reader Response Theory - Wahyu Unggul Widodo (Journalistics: Journal of English Teaching and Applied Linguistics, 2021)
The research’s purpose is to analyze cultural reader response strategies which are used by the reader to respond Dan Brown’s the Da Vinci Code novel. The objectives of the study are to know how readers respond religious views in the novel. This study is a qualitative study, the primary data source of the study is the responses from amazon.com customers and the guest who drop responds to the Da Vinci Code novel in amazon.com. The responses are from the paperback version and the secondary data sources of the study are books, internet, journals or any information related to reader response strategy. In analyzing the data, the writer employs descriptive analysis. The outcome of the study shows the readers are against with the idea about religion views in the novel, some are agreed with the idea and the others have neutral views. The dominant issue which is raised by the reader is a debatable problem in the novel dealing with Jesus marriage and having children, there is a great possibility it becomes a problematic because Brown’s initial statement in the beginning of the novel, “All descriptions of artwork, architecture, documents, and secret rituals in this novel are accurate.